2022
DOI: 10.1017/s1049023x22001133
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Longitudinal Study of Injuries and Medical Care, Assistance, and Losses Recounted by Oklahoma City Bombing Survivors after Nearly a Quarter Century

Abstract: Introduction: Terrorist incidents occur with alarming frequency. Much is known about acute injuries and psychopathology arising from terrorism, as well as medical care and functional status assessed in early post-disaster periods. Survivors’ memories of these experiences may change over subsequent decades, and their perspectives may evolve. Little information is available on how survivors describe these experiences decades later. Study Objective: This longitudinal qualitative study of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…50% or more of bombing-related PTSD and post-disaster MDD in the firefighters had not remitted at follow up. Similar to many other studies previously reviewed, few important predictors of remission were found, 13,14 especially in broader disaster-affected populations. This finding is also consistent with continuing work-related stress and hardship.…”
Section: Discussionsupporting
confidence: 84%
“…50% or more of bombing-related PTSD and post-disaster MDD in the firefighters had not remitted at follow up. Similar to many other studies previously reviewed, few important predictors of remission were found, 13,14 especially in broader disaster-affected populations. This finding is also consistent with continuing work-related stress and hardship.…”
Section: Discussionsupporting
confidence: 84%
“…Short-term studies do not necessarily contain all of the long-term findings collected decades later and do not necessarily reflect quantitative research findings because of conceptually different approaches to data collection. Quantitative long-term studies have generally demonstrated diminishing but some persisting postdisaster psychopathology (Bryant et al, 2021; Bui et al, 2021; Green et al, 1990; Lowe et al, 2020; van der Velden et al, 2013), including persistent PTSD or major depressive disorder in only 10%–20% of long-term survivors (North, McDonald, et al, 2022). Consistently, the longitudinal qualitative data in the current study did not reveal psychopathology to represent a major concern expressed decades after the bombing.…”
Section: Discussionmentioning
confidence: 99%
“…The large volume of the qualitative material collected necessitated the inclusion of three selected themes in this article: Thoughts and feelings , Coping , and Making meaning . Specific details of the other nine themes can be found in three other published articles from this study focused on these other themes (North et al, 2023; North, McDonald, et al, 2022; North, Suris, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%